Chicago Style for students and researchers - Turabian, Kate L (University of Chicago Press, 2013)
Includes bibliographical references (pages 409-433) and index.; Research and writing: from planning to production / Wayne C. Booth, Gregory C. Colomb, and Joseph M. Williams : What research is and how researchers think about it ; Moving from a topic to a question to a working hypothesis ; Finding useful sources ; Engaging sources ; Planning your argument ; Planning a first draft ; Drafting your report ; Presenting evidence in tables and figures ; Revising your draft ; Writing your final introduction and conclusion ; Revising sentences ; Learning from your returned paper ; Presenting research in alternative forums ; On the spirit of research -- Source citation : General introduction to citation practices ; Notes-bibliography style: the basic form ; Notes-bibliography style: citing specific types of sources ; Author-date style: the basic form ; Author-date style: citing specific types of sources -- Style : Spelling ; Punctuation ; Names, special terms, and titles of works ; Numbers ; Abbreviations ; Quotations ; Tables and figures -- Appendix: Paper format and submission.; This handbook is a set of guidelines to help students understand how to write, cite, and formally submit research writing.